Perceived Stress and its Triggers among Pharmacy University Students in Comparison to Student of Other Faculties: A Cross Sectional Study - Asdaq, Syed Mohammed Basheeruddin; Alshammari, Mohammed Kanan; Alsirhani, Asma Basheer; Alsirhani, Jawaher Basheer; Alshammari, Alhanoof Munawer; Imran, Mohd; Alamri, Abdulhakeem S.; Alhomrani, Majid; Alsanie, Walaa F.; Sreeharsha, Nagaraja (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: The role of stress in causing mental and physical damage is well known. The deleterious effect of stress is more dominant in young university students as they encounter repeated examinations amidst high expectation from the society. This study is an attempt to uncover the impact of stress on the university students and compare the level of stress among students of different health science programs. Materials and Methods: This cross-sectional comparative study was carried out using standardized and validated questionnaire by self-administration method. The questionnaire was distributed manually to the students at college of medicine, pharmacy and applied sciences at one of the accredited private universities of Saudi Arabia. The questionnaire contained demographic information, a perceived stress scale, stressors and stress relievers. The data was examined using analysis of variance and post-hoc testing. P≤0.05 was chosen as the statistical significance level. Results: Most of the respondents in this survey (73%) were between the ages of 18 and 25, with a balanced distribution of participants from medical (34%) pharmacy (33%) and applied sciences (33%) colleges. According to our statistics, the stress level among college of medical students was significantly greater than that of students in the college of applied sciences. Furthermore, on the perceived stress scale, students from both the college of pharmacy and the college of medicine reported higher levels of stress. Academic difficulties were a major source of stress for most students. Conclusion: Students in all three fields of study reported feeling anxious, although it shows that applied science college students are less stressed than medical and pharmacy students. The most major stressors are academic variables, prompting the development of specific and targeted treatments to significantly reduce the stress burden on students. Students’ needs should be addressed through teaching methods and academic atmosphere. Finally, students can lower their stress levels by acquiring effective study habits and time management skills.
Keywords: Stress; University students; Stress relievers; Medicine; Pharmacy; Applied; Science; Stress management